The experience of self-advocacy among cancer patients: A qualitative meta-synthesis - Lijun Lin; Ying Jin; Chunxiao Feng; Kejia Zhu (PLoS ONE, 2025)
Background During cancer treatment, patients are faced with major changes in physical function, psychological challenges and decline in quality of life. Self-advocacy is a key tool for patients to cope with the challenges of treatment. By fostering self-advocacy, patients can effectively self-manage, enhancing their overall quality of life and treatment outcomes. Besides, a significant majority of cancer patients encounter barriers when attempting to articulate their healthcare needs and engage in treatment decision-making processes. It’s important to identify obstacles in the process of self-advocacy. The aim of this meta-synthesis was to describe the patients’ experience of self-advocacy, and identify the facilitators and barriers of self-advocacy for cancer patients. Methods The review used the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines guided reporting, and appraised the quality of each eligible study using the Critical Appraisal Skills Programme (CASP) checklist. A prospective review protocol was registered in the International Prospective Register of Systematic Reviews(no: CRD42023493926). A qualitative meta-synthesis was performed by searching eight electronic databases, including PubMed, Web of Science, Embase, Ovid MEDLINE, CINAHL, CNKI, Wanfang and SinoMed for studies meeting pre-defined eligibility criteria, from inception to November, 2023. Two reviewers independently undertook screening and review of articles, using the CASP checklist for evaluating qualitative research. The data were synthesised using Thomas and Harden’s method of thematic and content analysis. Results A total of 7 papers were included, and 24 research findings were distilled and integrated into three themes: benefits; challenges; external environmental support; and seven sub-themes: Gain confidence; improve self-management ability; Interaction and share; lack of awareness; obstacles; health system support and social support. Conclusions Cancer patients have different levels of self-advocacy ability, which is the result of the interaction between personal consciousness and family and social environment. Factors influencing self-initiative include patient gender, personality characteristics, support from friends and family, and support from the medical system. Therefore, medical staff should pay more attention to cancer patients with weak awareness of self-advocacy and poor enthusiasm and can use patient friend exchange meetings and entertainment interventions to improve patients ‘level of self-advocacy. Future interventions should comprehensively consider the characteristics of cancer patients themselves and their external environment, and engage in multidisciplinary team cooperation.